The Buzz Group Technique For Teaching Reading Comprehension Of Recount Text Of The Eight Grade Students Of Junior High School - Ananda Sintani (Proceedings of The ICECRS, 2021)
The purpose of this study was to solve the problems that existed in grade 8 smpn 2 Buduran namely students' reading comprehension. By using group buzz techniques to improve reading comprehension through recount text. This research uses quantitative methods, through several tests consisting of try outs, pre-tests and post-tests. Some tests are carried out in some time. Before using the group buzz technique students are given a pre-test test. The result of the pre-test was 75. After the pre-test, the use of group buzz technique was applied to the students and then the students worked on the post-test. The result of the post test is 87.42 It can be concluded that the post-test results are greater than the pre-test. This shows that the group buzz technique can improve students' reading ability in recount text material.